DESIGN RANGE CRITERIA IN DESIGNING OF CONTROLLED ASYNCHRONOUS MOTORS - Petrushin, V. S.; Jenoktajev, R. N. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2014)
The paper presents automated optimization designing of regulated induction motors accomplished for a variety of design problems under two range criteria. Design tasks involve consideration of both static and dynamic modes. Dependence of change in the motors variable parameters on the criterion chosen and the designing objectives is determined.